Aménagements de berge monumentaux d’époque laténienne et romaine à Besançon (Doubs) - Christophe Gaston (Gallia)
Several successive phases of development of the banks of the Doubs river were identified during excavations at the site of “parking des Remparts Dérasés” in Besançon (Doubs) carried out by Inrap in 2002. All of these sequences cover a period from the end of the 2nd c. BC to the present day. As regards the protohistoric period, initial development work was carried out on the bank in the form of a dry wall (end of the 2nd c. BC) built with undressed limestone blocks of highly heterogeneous sizes. This development was followed by an imposing murus gallicus which is dated to about 80 BC and possibly corresponds to that quoted by Caesar. Its front is located 2 m in front of the facing of the previous bank wall, which it completely incorporates. The timber framework of the internal mass of the rampart is characterised by a tight interweaving of beams and by the unusual size of the iron spikes that ensure the cohesion of this interlocking framework. These characteristics are undoubtedly linked to the particular situation of the rampart on the river bank. At the rear of the rampart a road paved with alluvial pebbles has been uncovered that separated this structure from the residential area. The preserved starting point of the internal slope along this path makes it possible to estimate the width of the rampart as being 6 m for a height that must have been around 4,5 to 5 m at the level of the parapet walkway. A recessed area in this masonry could correspond to a postern-gate to access the landing stage. During the Roman period, a monumental embankment, with a sloping facing made entirely of dry stone, was created under the reign of Tiberius. The maximum preserved height is 2,25 m, but it can be estimated, thanks to the levels of roadways that lean against it, that its total height reached almost 4 m, and its maximum width exceeded 10 m in places. The facade has the peculiarity of being erected along the very regular profile of a stepped slope, whose gradient, at a constant angle of almost 53° to the horizontal, made it possible to highlight the use of the Pythagorean triangle. This embankment is interrupted by the gravel ramp of a landing stage which descends to a quay formed by a line of large parallelepiped blocks. Two mooring pilings have also been uncovered along the embankment, upstream of the slipway.